Data mining powered by the gene ontology. (12th February 2020) - Manda, Prashanti
Abstract: The gene ontology (GO) is a widely used resource for describing molecular functions, biological processes, and cellular components of gene products. Since its inception in 2006, the GO has been used to describe millions of gene products resulting in a massive data store of over 6 million annotations. The staggering amount of data that has resulted from annotating gene products with GO terms has led the way and opened new avenues for a wide variety of large‐scale computational analyses. Specifically, a variety of data mining techniques such as association rule mining, clustering etc. have been applied successfully to a range of biological applications. This article provides a review of four data mining applications/techniques for GO data mining gene expression data, association rule mining, clustering, and text mining and highlights future directions in each of these areas. This article is categorized under: Algorithmic Development > Association Rules Algorithmic Development > Biological Data Mining Ensemble Methods > Text Mining Abstract : An overview of data mining applied to the Gene Ontology.